“The Doctor” Teaches Humanities to Medical Students - Alis Ozcakir; Nazan Bilgel (European Scientific Journal, ESJ, 2018)
Education in humanities is an important part of medical curriculum. With traditional didactic approaches, it is difficult to teach humanities. Using movies and other audio-visual materials can make the teaching of humanities for medical students easier. We used “The Doctor” movie during our family medicine course for educating the last year medical students about communication and patient-doctor relationships, which belongs to the core elements of medical humanities. The movie was evaluated by the students through a questionnaire with structured and open-ended questions and was discussed in the classroom. This study reports the findings of the students’ selfreports and discussions. The overall rating of the movie was 2.5 on a five point Likert scale. There was no significant difference in terms of rating among male and female students. Most of the students found this movie little or not at all emotional. Most of the students reported a positive emotional impact of the movie. Most of the students found the movie more useful than lectures (90.9 %) and journal articles (90.9 %) in teaching the patient-doctor relationships. This proportion was 54.5 % compared to bedside rounds and this finding revealed that students accept the bedside rounds as an important component of learning patient-doctor relationships. We concluded that movies should be an enhancement tool for the curriculum, but not the curriculum. The curriculum with some instructional goals such as understanding, reasoning, critical thinking, and reflection should guide the use of movies.